2015
DOI: 10.1016/j.envsci.2014.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Contexualising the tool development process through a knowledge brokering approach: The case of climate change adaptation and agriculture

Abstract: This article applies a 'knowledge brokering' approach to contextualise the development of an integrated computer modelling tool into the real world policy context of adaptation of agriculture to climate change at the EU level. In particular, the article tests a number of knowledge brokering strategies described and theorized in the literature, but seldom empirically tested. The article finds that while the policy context can be used to identify a theoretically informed knowledge brokering strategy, in practice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 17 publications
1
12
0
1
Order By: Relevance
“…While initially the policy developers had an intention to employ LEAP among other models in Energy Plan 2030+, then in the course of the plan development the intention was dropped since the other previously chosen models (AirViro and SimaPro, Table 1) also provided an opportunity to project the energy sector emissions and no specific task was foreseen for LEAP. Hence, the tool selection could be seen as a competition between different researchers to have 'their' tools used in the policy making process -as Adelle (2014) noted that in practice it is questionable whether the tool choice depends more on tool design and communication or it can be characterised by a high level of competition. The researchers, however, were not in the position of neutral facilitators of knowledge exchange here, but rather sought to broker their own knowledge and model.…”
Section: Discussionmentioning
confidence: 96%
“…While initially the policy developers had an intention to employ LEAP among other models in Energy Plan 2030+, then in the course of the plan development the intention was dropped since the other previously chosen models (AirViro and SimaPro, Table 1) also provided an opportunity to project the energy sector emissions and no specific task was foreseen for LEAP. Hence, the tool selection could be seen as a competition between different researchers to have 'their' tools used in the policy making process -as Adelle (2014) noted that in practice it is questionable whether the tool choice depends more on tool design and communication or it can be characterised by a high level of competition. The researchers, however, were not in the position of neutral facilitators of knowledge exchange here, but rather sought to broker their own knowledge and model.…”
Section: Discussionmentioning
confidence: 96%
“…Together these trends have created an increasing need to provide a continuous overview of the vast amounts of knowledge generated. In many countries, these concerns have led to the creation of special agencies or clearinghouses given the task to act as knowledge broker by translating research-based evidence into policy and practice (e.g., Adelle, 2015;Kislov, Wilson, & Boaden, 2017;Moore, Redman, D'Este, Makkar, & Turner, 2017). So far, knowledge brokering has become a significant activity in medicine and health, transport, and social welfare (Burns & Schuller, 2007;Moore et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, to our knowledge no study to date has quantitatively demonstrated the value of using knowledge brokers to connect scientists and decision‐makers in relation to environmental challenges, nor comprehensively documented the ways in which knowledge brokers can add value to knowledge exchange processes. This is, in part, due to the lack of established methods to evaluate the effectiveness and efficiency of knowledge brokers, or the types of activity they undertake (Fazey et al , ; Adelle, ).…”
Section: Introductionmentioning
confidence: 99%